Pengaruh Kualitas dan Kuantitas Pakan (Daun Bawang) terhadap Kejadian Polimorfisme Warna pada Larva Spodoptera exigua Hubner (Lepidoptera: Noctuidae) - CRUZ, LATIZIO BENI DA COSTA; SUPARTHA, I WAYAN; SUSILA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 8 No 2 (2018)DO - 10.24843/AJoAS.2018.v08.i02.p03, 2019)
The Effect of Feed (Onion Leaves) on the Event of Color Polymorphism on Larvae Spodoptera exigua HUBNER (Lepidoptera: Noctuidae) . Color polymorphism is a form of color difference that appears morphologically and genetically in the same insect species. The existence of these changes in shape has to do with the defense mechanism of the species concerned for disguise, avoiding natural enemies and adjusting to the new environment. The occurrence of color polymorphism is often found in S. exigua larvae that attack the onion crop in the field. The purpose of the study was to determine the effect of the quality and quantity of feed (onion) on the color changes of S. exigua larvae. This research was carried out in the laboratory using adaptation test method and comparative test with randomized block design. The results of the study show that decreasing the quality and quantity of feed (onion) encourages color changes from green to dark. In addition, green to dark color changes are also triggered by the developmental phase of the larvae. The development of larvae from the 3rd instar phase has shown symptoms of color change from green to dark even though the quantity and quality of the food is fulfilled.